Manure matters: prospects for regional banana-livestock integration for sustainable intensification in South-West Uganda. Issue 5 (3rd September 2022) - Braber, Harmen den; van de Ven, Gerrie; Ronner, Esther; Marinus, Wytze; Languillaume, Antoine; Ochola, Dennis; Taulya, Godfrey; Giller, Ken E.; Descheemaeker, Katrien
ABSTRACT: In South-West Uganda, manure is highly valued for sustaining yields of East African Highland Banana, but it is in short supply. As a result, banana growers import manure from rangelands up to 50 km away. We aimed to explore the potential of this regional banana-livestock integration to meet crop nutrient requirements for sustainable intensification of banana cropping systems. We used a mixed-methods approach supported by detailed data collection. Multiple spatial levels were integrated: field-level modelling to determine long-term nutrient requirements, a household-level survey to characterize farmer practices, and a regional-level spatial analysis to map banana production and manure source areas. For median to 90 th percentile banana yields (37-52 t FW/ha/year), minimum K requirements were 118–228 kg/ha/year. To supply this with manure, 10.5–20.5 t DM manure/ha/year would be needed, requiring 47–91 tropical livestock units and 27–52 ha of rangeland, far more than what is potentially available currently. However, using only manure to satisfy potassium requirements increases the risk of N losses due to nutrient imbalances likely to result from large manure applications. For sustainable intensification, manure supplemented with K-based fertilizers is a better option than manure alone, as it is more cost-effective and reduces potential N losses.